Association and interactions between mixed exposure to trace elements and the prevalence of kidney stones: a study of NHANES 2017–2018 - Wang, Xiao; Zhang, Jia; Ma, Zhibin; Yang, Yaya; Dang, Ying; Cao, Shuting; Shi, Xiaoru; Ouyang, Changping; Pan, Jinhua; Hu, Xiaobin (Frontiers in Public Health, 2023)
The association between exposure to trace elements mixture and the prevalence of kidney stones and the interactions between elements are unclear. The aim of this study was to explore the association between exposure to trace elements mixture and the prevalence of kidney stones and the interactions between the elements. Methods A total of 1244 subjects (age >20 years)participants (139 kidney stone formers and 1105 non-stone former participants) in NHANES 2017-2018 were included. The exposure to trace elements was evaluated by measuring their concentration in urine samples. Three methods, Logistic regression, quantile-based g computation (qgcomp), and Bayesian kernel machine regression (BKMR), were used for analysis. Results According to the results from qgcomp and BKMR, Aa negative association was found between exposure to the 13 trace elements and the prevalence of kidney stones (OR = 0.50 [0.32, 0.78]). Subgroup analysis revealed that Co, As and iodine in the whole population, Co, As, and Ni in males, and Cs, iodine, and Sb in females, were most strongly associated with kidney stones. Kidney stone was found to be positively correlated with Co and negatively correlated with the other elements. Besides, there were significant interactions between Ni and Pb in the whole population, Co and iodine in males, and Pb and iodine in females.There was a negative association between exposure to the mixture of 13 trace elements and the prevalence of kidney stones. This is a provisional file, not the final typeset article Kidney stones are widely prevalent, and the prevalence of kidney stones has shown an increasing trend over the years worldwide. The self-reported prevalence of kidney stones among adults aged 20 years and older in the United States was 3.